Adaptive interval type-2 fuzzy neural network nonsingular fast terminal sliding mode control for cable-driven parallel robots - Oghabi, Emad; Kardehi Moghaddam, Reihaneh; Kobravi, Hamid Reza (Engineering applications of artificial intelligence, 2024)
Since the cable-driven parallel robots (CDPRs) are subject to the model uncertainty and external disturbances with high nonlinearity, classic trajectory tracking control approaches cannot guarantee a finite-time and robust controlling performance. To solve this problem, the paper proposes a novel adaptive interval type-2 fuzzy neural network non-singular fast terminal sliding mode control (AIT2FNN-NFTSMC) approach, which provides a high precision finite-time robust closed-loop control system. Firstly, a non-singular fast terminal sliding manifold is introduced and then, the fast singular free control law is designed to reach the fast finite-time convergence of the CDPR states to the desired trajectories. Meanwhile, an interval type-2 fuzzy neural network (IT2FNN) system is constructed to approximate the unknown nonlinearities and the uncertainties, and the adaptive control law is realized. The finite-time stability of the closed-loop control system is proved using the Lyapunov stability theorem. Finally, numerical simulations are reported to demonstrate the effectiveness of the proposed controller method.